Impact of clinical features, cytogenetics, genetic mutations, and methylation dynamics of CDKN2B and DLC-1 promoters on treatment response to azacitidine - Martín, Iván; Navarro, Blanca; Serrano, Alicia; Villamón, Eva; Calabuig, Marisa; Solano, Carlos; Chaves, Felipe Javier; Yagüe, Nuria; Orts, Maribel; Amat, Paula; Fuentes, Azahara; Seda, Enrique; et al. (Annals of hematology, 2020)
Azacitidine (AZA) is a DNA hypomethylation agent administered in myeloid neoplasms; however, there is still a lack of established predictors of response. We studied 113 patients with myelodysplastic syndromes ( n = 85) or acute myeloid leukemia ( n = 28) who received AZA to assess the predictive value on response of clinical features, cytogenetics, and molecular markers. Overall, 46 patients (41%) responded to AZA. Platelet doubling after the first AZA cycle was associated with a better response (68% vs. 32% responders, P = 0.041). Co-occurrence of chromosome 7 abnormalities and 17p deletion was associated with a worse response ( P = 0.039). Pre-treatment genetic mutations were detected in 98 patients (87%) and methylation of CDKN2B and DLC-1 promoters were detected in 50 (44%) and 37 patients (33%), respectively. Patients with SF3B1 mutations showed a better response to AZA (68% vs. 35% responders, P = 0.008). In contrast, subjects with mutations in transcription factors ( RUNX1 , SETBP1 , NPM1 ) showed a worse response (20% vs. 47% responders, P = 0.014). DLC-1 methylation pre-treatment was associated with poor clinical features and its reduction post-treatment resulted in a better response to AZA in MDS patients ( P = 0.037). In conclusion, we have identified several predictors of response to AZA that could help select the best candidates for this treatment.